Effect of Parachute Running Training on 100 Meter Sprint Running Speed - suharti, suharti; Harwanto, Harwanto; BP, Ismawandi (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2021)
This study aims to determine how much influence the parachute running exercise has on the 100-meter sprint running speed of class X MA Darul Ulum Waru Sidoarjo. This research is quantitative research with experimental method. The research design used was One Group Pretest and Posttest Design, namely experiments carried out in one group without a comparison group. While the sample in this study found 20 students at MA Darul Ulum Waru Sidoarjo. Results Based on the research, it is known that the minimum pretest value is 15.28, the maximum is 21.09, while the posttest value is at least 15 and the maximum is 16.72, while the sig. (2-tailed) in the experimental group is 028, so the value of sig (2-tailed) < 0.05, it can be said that Ho is rejected and accepted, it can be said that there is an effect on running training using Parachute Running on sprint running speed 100 meters (Students of Class X MA Darul Ulum Waru Sidoarjo). From the results of this study, it is hoped that running exercises using Parachute Running can be a reference as a variation of sprint running exercises so that they are not monotonous.Keywords: parachute running, 100 meter sprint.